1986
DOI: 10.1128/jb.165.2.467-473.1986
|View full text |Cite
|
Sign up to set email alerts
|

Genes for Bacillus megaterium small, acid-soluble spore proteins: cloning and nucleotide sequence of three additional genes from this multigene family

Abstract: Three genes coding for small, acid-soluble spore proteins (SASP) were cloned from Bacillus megaterium, using previously cloned B. megaterium SASP genes (SASP-C and -C-3) as DNA-DNA hybridization probes. One gene (SASP-A) codes for the A protein, a previously identified major SASP. The other two (termed genes for SASP-C-4 and -C-5) are extremely similar in much of their nucleotide sequence to the previously cloned B. megaterium SASP-C-2 gene. The proteins coded for by all these SASP genes had extensive sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 17 publications
1
30
0
Order By: Relevance
“…1, lane b). This is exactly the result predicted if this pJH101 derivative had integrated into the chromosome by a Campbell-type mechanism at the site of the SASP-A gene (7). Similar analyses of drug-resistant clones derived from transformation with pJH101 derivatives carrying the SASP-C, SASP-C-3, SASP-C-4, or gpr gene indicated that these plasmids had also integrated into the chromosome by a Campbell-type mechanism at the site of the cloned gene carried on the transforming plasmid (data not shown).…”
supporting
confidence: 71%
See 2 more Smart Citations
“…1, lane b). This is exactly the result predicted if this pJH101 derivative had integrated into the chromosome by a Campbell-type mechanism at the site of the SASP-A gene (7). Similar analyses of drug-resistant clones derived from transformation with pJH101 derivatives carrying the SASP-C, SASP-C-3, SASP-C-4, or gpr gene indicated that these plasmids had also integrated into the chromosome by a Campbell-type mechanism at the site of the cloned gene carried on the transforming plasmid (data not shown).…”
supporting
confidence: 71%
“…There are two major types of SASP in B. megaterium, type A/C and type B, which differ significantly from each other in amino acid sequence (6,11). While there is only a single type B SASP gene, there are at least seven genes which code for type A/C SASP of extremely similar amino acid sequence, with two of these genes coding for the two major SASP of this type, termed SASP-A and SASP-C in B. megaterium (6)(7)(8)11). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas several other weakly hybridizing bands were seen in some digests (lanes d to f), the relative intensity of these bands was very much lower than that of the major band. In contrast, the various members of the SASP A and C gene family cross-hybridized much more strongly even under more restrictive hybridization conditions (55°C) (2,3,8). It is, of course, possible that there are multiple SASP B-like genes in B. megaterium but that they are not highly conserved and thus hybridize only very weakly to the SASP B probe.…”
Section: 'mentioning
confidence: 86%
“…The amino acid sequences of these proteins are known, and those of SASP A and C are extremely similar, whereas that of SASP B is much less closely related (14)(15)(16)(17). This system appears even more complex at the gene level because, in addition to the genes coding for SASP A and C, there are five other genes that code for proteins with amino acid sequences extremely similar (70 to 90% sequence identity) to those of SASP A and C (7)(8)(9). All of these closely related SASP Aand C-like genes are expressed in parallel midway in sporulation, although some (SASP A and C genes) are expressed at much higher levels than others (7)(8)(9).…”
mentioning
confidence: 99%